Need for a "Cull Survey" in Indian Forests - Sangal, P. M. (Indian Forester, 1967)
The terms Cull, Cull wood alld Cull Factor are proposed for use in Indian Forestry. The need for conducting a regular Cull Survey within the frame work of the proposed National Forest Survey in conjunction with the specialists in different fields and State Forest Departments has been stressed.